2011
DOI: 10.1038/labinvest.2011.125
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin improves skin wound healing and activates the TGF-β signaling pathway

Abstract: We could recently report that erythropoietin (EPO) accelerates skin wound healing in mice. Now, we provide insight into the molecular mechanisms of this non-hematopoietic property of EPO analyzing the transforming growth factor (TGF)-b signaling pathway. EPO receptor was found expressed in both non-wounded and wounded skin tissue as well as in fibroblasts and keratinocytes. In saline-treated control animals, wounds exhibited a significant upregulation of TGF-b1 and of a-smooth muscle actin (a-SMA) compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 33 publications
1
29
0
3
Order By: Relevance
“…Furthermore, we present in vivo evidence that BNIP3-induced UCB-hMSCs transplantation by hypoxia pretreatment or PA accelerates myoblast switch and blood vessel formation, as well as the skin wound healing process. A phenotypic switch of fibroblasts toward myofibroblasts via myofibroblast development has been reported as a representative characteristic of wound repair and maturation [80], [81]. Although transplanted UCB-hMSCs at the wound site are exposed to hypoxia, due to low density of vascular distribution, BNIP3 silencing of UCB-hMSCs with normoxia pretreatment did not significantly affect this process.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we present in vivo evidence that BNIP3-induced UCB-hMSCs transplantation by hypoxia pretreatment or PA accelerates myoblast switch and blood vessel formation, as well as the skin wound healing process. A phenotypic switch of fibroblasts toward myofibroblasts via myofibroblast development has been reported as a representative characteristic of wound repair and maturation [80], [81]. Although transplanted UCB-hMSCs at the wound site are exposed to hypoxia, due to low density of vascular distribution, BNIP3 silencing of UCB-hMSCs with normoxia pretreatment did not significantly affect this process.…”
Section: Discussionmentioning
confidence: 99%
“…The increased levels of TGF-b1 in Acalypha indica treated rats substantiate the results of Atiba et al (2011) in which they have used Aloe vera and found increased healing through enhanced expression of TGF-b1. Siebert et al (2011) have reported that erythropoietin accelerates wound closure by activating the TGF-b signaling pathway which is responsible for enhanced differentiation of myofibroblasts. Aloe vera was found to augment and accelerate acute radiation-delayed wound healing by increasing the expression of TGF-b1 (Atiba et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we performed immunohistochemistry (IHC) on human lung ADC tissue microarrays (TMAs) using anti-DOCK4-specific and anti-p-Smad3-specific antibodies (Supplemental Fig. 2A; Siebert et al 2011). We observed that DOCK4 expression was significantly higher in tumor tissues compared with adjacent normal tissues (Supplemental Fig.…”
Section: High Dock4 Expression Correlates With Smad Activation and Pomentioning
confidence: 99%